2009
DOI: 10.1038/sc.2009.178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the physical activity scale for individuals with physical disabilities in people with spinal cord injury

Abstract: Study design: Cross-sectional study. Objectives: To evaluate the physical activity scale for individuals with physical disabilities (PASIPD) in people with spinal cord injury (SCI). Setting: Eight Dutch rehabilitation centers with a specialized SCI unit. Methods: The PASIPD was examined by comparing group scores of people with different personal (age, gender and body mass index) and lesion characteristics (level (paraplegia/tetraplegia), completeness, time since injury (TSI)) in 139 persons with SCI 1 year aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 17 publications
4
29
1
4
Order By: Relevance
“…Our study confirms that during the primary rehabilitation program, housework skills training is given too little attention and people with SCI after discharge at home have a lot of problems. The authors [25,38] agrees with our study results, and state, that the activity in housework's is improving with each year after SCI onset by naturally engaging in different life situations, and authors recommends that during inpatient rehabilitation currently pay more trainings and purposeful activities for housekeeping skills. Krause et al [22] in the longitudinal studies confirm our findings, that people after SCI onset mostly in long-term period go to the field and going to handle social affairs.…”
Section: Discussionsupporting
confidence: 81%
“…Our study confirms that during the primary rehabilitation program, housework skills training is given too little attention and people with SCI after discharge at home have a lot of problems. The authors [25,38] agrees with our study results, and state, that the activity in housework's is improving with each year after SCI onset by naturally engaging in different life situations, and authors recommends that during inpatient rehabilitation currently pay more trainings and purposeful activities for housekeeping skills. Krause et al [22] in the longitudinal studies confirm our findings, that people after SCI onset mostly in long-term period go to the field and going to handle social affairs.…”
Section: Discussionsupporting
confidence: 81%
“…To our knowledge, only one previous study has assessed this relation in persons with a recent SCI. 10 In that study, in which a questionnaire was used to ascertain activity level, a weak correlation was found. More research is necessary to elucidate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This relation has also been studied in persons with a SCI. [5][6][7][8][9][10][11] However, these studies all used questionnaires to determine physical activity level. Although studies have shown that when using questionnaires there is a risk of overestimation and that self-reported activity level is only weakly related to objectively measured activity level.…”
Section: Introductionmentioning
confidence: 99%
“…Fizinis aktyvumas ugdo ir stiprina visas organizmo sistemas ir jo funkcijas, yra naudingas įvairių sveikatos sutrikimų prevencijai, didina fizinį pajėgumą [1,4,2,10]. Nors fizinis aktyvumas yra labai svarbus lėtinių ligų prevencijai, tačiau tyrimai rodo, kad vis mažiau žmonių leidžia laisvalaikį fiziškai aktyviai [4,3]. PSO 2010 metų duomenimis, nepakankamas fizinis aktyvumas yra ketvirta pagal dažnį bendrojo mirtingumo priežastis.…”
Section: įVadasunclassified